Prevalence and risk factors of hepatitis B and C viruses among haemodialysis patients: a multicentric study. Issue 1 (January 2019) - Ali, Niyaz; Hussain, Wajid; Hayat, Azam; Shah, Tariq; Wen, Ronghui; Zeb, Ifra; Abdul Malik, Attiya; Ramzan, Rahdia; Rehman, Mujaddad-ur; Khan, Ibrar
Abstract : Background: Hepatitis B virus (HBV) and hepatitis C virus (HCV) infections are important causes of morbidity and mortality among haemodialysis (HD) patients and create problems in the management of patients in the renal dialysis units, as patients with chronic renal failure do not absolutely clear these viral infections. Aim: The aim of the study is molecular detection of HBV and HCV and their possible risk factors among the HD patients in northern Pakistan. Materials and methods: A cross-sectional study was conducted from November 2013 to June 2014. The infections were investigated through serological and molecular techniques. Results: The overall prevalence of HBV among the five HD centres was 7.5%. The main risk factors were HD centre (26.66%), history of blood transfusion (20%), dental procedure (13.33%) and time duration on HD (6.66%). However, the overall prevalence of HCV among the five HD centres was 19.58%. The main risk factors included HD centre (25.53%), history of blood transfusion (25.53%), dental procedure (10.64%), surgical treatment (6.38%), patients treated abroad (6.38%) and time duration on HD (4.25%). Conclusion: The high prevalence of hepatitis viruses among HD patients of northern Pakistan indicates a close relation between HD centres and hepatitis virus transmission. Therefore, preventive control measures are essential to reduce hepatitis transmission in HD centres.